A Phenomenological Study of Federally Funded School Counselor Educators’ Non-Dual Educator-Counselor and Antiracist School Counselor Identity - Yung-Yu Lee; Matthew Lemberger-Truelove (Teaching and Supervision in Counseling, 2024)
School counselor educators train future professionals who will adopt a non-dual educator-counselor identity and deliver direct services to culturally diverse students and other education stakeholders. To capture select school counselor educators’ values and practices, the authors of the current study performed a descriptive phenomenological study using semi-structured interview questions to elicit the experiences of six school counselor educators who received federal funding to increase the diversity and quality of mental health services in public schools. Findings included the following five themes: 1) perspectives of professional identity; 2) equity, social justice, and inclusion; 3) pedagogical strategies in training program; 4) collaboration and partnerships; and 5) rewards and challenges in counseling education. Implications related to counselor education and future research are discussed.
Keywords: anti-racism; counselor education; educator-counselor; school counselors